2006
DOI: 10.1248/bpb.29.354
|View full text |Cite
|
Sign up to set email alerts
|

Water Extract of Cordyceps militaris Enhances Maturation of Murine Bone Marrow-Derived Dendritic Cells in Vitro

Abstract: Water extract (WE) of Cordyceps militaris has been reported to produce antitumor and immunomodulatory activities in vivo and in vitro. However, the therapeutic mechanism has not been known. In this study, we investigated whether water extract of C. militaris induces the phenotypic and functional maturation of dendritic cells (DC). It profoundly increased CD40, CD54, CD80, CD86, and MHC class II expression in murine bone marrow (BM)-derived myeloid DC. Endocytosis was assessed by the uptake of FITC-dextran and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…CM also contains higher concentration of cordycepin than CS (Yu et al, 2006). Cordycepin from C. militaris has been reported to have acute anti-inflammatory, anti-nociceptive, anti-angiogenesis and immunoregulatory activities (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CM also contains higher concentration of cordycepin than CS (Yu et al, 2006). Cordycepin from C. militaris has been reported to have acute anti-inflammatory, anti-nociceptive, anti-angiogenesis and immunoregulatory activities (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These mushroom extracts induce phenotypic and functional maturation of dendritic cells, tumoricidal activity in macrophages, and augmentation of natural killer cell activity [Sorimachi et al, 2001;Kodama et al, 2005;Kim et al, 2006]. It has also been shown that oral administration of mushroom extracts has an anti-inflammatory effect [Bernardshaw et al, 2006] and decreases IgE levels through modulation of the Th1/Th2 balance [Inagaki et al, 2005;Lim et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, plantderived polysaccharides have been suggested as promising candidates for DC maturation. For example, PL polysaccharide from Phellinus linteus [31], a proteoglycan from Agaricus blazei [32], PSK from Coriolus versicolor [33], a polysaccharide from Cordyceps militaris [34], angelan from Angelica gigas Nakai [16], and acemannan from Aloe vera [35] have been found to induce phenotypic and functional maturation of murine immature DCs. Here, we demonstrate that sparan might also be a good inducer of DC maturation.…”
Section: Discussionmentioning
confidence: 99%